NURSING CARE FOR PATIENTS AT RISK OF VIOLENT BEHAVIOR BY PROVIDING MODALITY THERAPY OF SPIRITUAL SNAKE AND LADDER GAME IN THE NAKULA PSYCHIATRIC INSTALLATION OF BANYUMAS REGIONAL HOSPITAL: CASE REPORT - Wahyudi Mulyaningrat; Adinda Virni Arida (International Journal of Biomedical Nursing Review, 2024)
Introduction: Violent behavior is a response to anger that is expressed by making threats, injuring oneself or others and can damage the surrounding environment. One way of treating patients at risk of violent behavior can be done using pharmacology or non-pharmacology. One of the non-pharmacological therapies used is the snakes and ladders game approach. This type of therapy considers the goals and benefits, including being able to stimulate the players' cognitive, language, emotional and socio-spiritual functions. The aim of this research is to find out whether spiritual snakes and ladders modality therapy can reduce signs and symptoms of risk of violent behavior (RPK). Methods: The type of method that has been used in the case study uses modality therapy through the medium of the snakes and ladders game which has been technically modified or the game method is carried out using a spiritual therapy approach. Discussion: Based on the research results, it shows that the signs and symptoms of the risk of violent behavior that previously appeared in patients no longer appear after the spiritual snakes and ladders modality therapy was given. Conclusion: Implementation of nursing care provided to patients Mr. S with modality therapy using spiritual snakes and ladders media is an effective way to reduce several signs and symptoms of the risk of violent behavior.